Moral message on metaphoric short children narrative - Muzaki, Ferril Irham (University of Antwerp, Belgium, 2021)
This study aims to (1) to describe moral messages that are packaged in metaphors in international children's narrative, (2) to analyze moral messages that are packaged in metaphors in international children's narrative, and (3) to encode the metaphors used in international children's narrative. This research uses theme analysis. The research data in this study are the form of phrases, clauses, and sentences that contain moral messages. The data source of this research is children's narrative on the internet. This research produces findings that metaphors used to package moral messages in children's films consist of nine forms, namely 1) animal metaphors (2) everyday metaphors,(3) situation metaphors, (4) natural metaphors, (5) symbolic metaphors, (6) association metaphor, (7) diverse metaphor, (8) environment metaphor and (9) landscape metaphor. The conclusion of this study is the moral message for learning materials in elementary schools delivered in the form of children's narrative that are packaged in the form of metaphors. Keywords: children's narrative; moral messages; theme analysis; universality; metaphors